2019
DOI: 10.1111/acel.12922
|View full text |Cite
|
Sign up to set email alerts
|

α‐Synuclein toxicity in yeast and human cells is caused by cell cycle re‐entry and autophagy degradation of ribonucleotide reductase 1

Abstract: α‐Synuclein (aSyn) toxicity is associated with cell cycle alterations, activation of DNA damage responses (DDR), and deregulation of autophagy. However, the relationships between these phenomena remain largely unknown. Here, we demonstrate that in a yeast model of aSyn toxicity and aging, aSyn expression induces Ras2‐dependent growth signaling, cell cycle re‐entry, DDR activation, autophagy, and autophagic degradation of ribonucleotide reductase 1 (Rnr1), a protein required for the activity of ribonucleotide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Due to its DNA-binding properties, a regulating role in transcription has been suggested ( Martins et al, 2011 ) which could result in the miRNA and gene expression alterations observed in our model. Furthermore, in accordance with our findings, an emerging body of evidence has linked PD and αSyn to cell cycle processes ( Lee et al, 2003 ; Höglinger et al, 2007 ; Ma et al, 2014 ; Paiva et al, 2017 ; Sampaio-Marques et al, 2019 ). An increased number of proteins associated with DNA synthesis and cell cycle re-entry was reported in dopaminergic neurons of postmortem PD brain tissue ( Höglinger et al, 2007 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Due to its DNA-binding properties, a regulating role in transcription has been suggested ( Martins et al, 2011 ) which could result in the miRNA and gene expression alterations observed in our model. Furthermore, in accordance with our findings, an emerging body of evidence has linked PD and αSyn to cell cycle processes ( Lee et al, 2003 ; Höglinger et al, 2007 ; Ma et al, 2014 ; Paiva et al, 2017 ; Sampaio-Marques et al, 2019 ). An increased number of proteins associated with DNA synthesis and cell cycle re-entry was reported in dopaminergic neurons of postmortem PD brain tissue ( Höglinger et al, 2007 ).…”
Section: Discussionsupporting
confidence: 92%
“…Similar observations were made in cellular and animal models of PD ( Lee et al, 2003 ; Paiva et al, 2017 ). The atypical re-entry of post-mitotic dopaminergic neurons into the cell cycle is believed to cause apoptosis ( Sampaio-Marques et al, 2019 ), as well as nuclear accumulation of αSyn in PC12 cells ( Ma et al, 2014 ). Both of these effects were shown to promote neurotoxicity through cell cycle activation ( Ma et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies underline the relevant role of cellular models for a better understanding of the molecular regulation of human pathologies [15]. As such, budding yeast has been extensively employed in models of synucleinopathies [16][17][18][19]. In addition, an age-related degeneration of dopaminergic neurons has been shown in wild-type C. elegans [20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, is there a single core regulator of multiple radiation resistance-related signaling pathways, active during all radiation resistance processes? [23, 24].
Fig.
…”
Section: Introductionmentioning
confidence: 99%